2007
DOI: 10.1177/1077801207305217
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Women and Tolerance for Sexual Harassment Among Reservists

Abstract: Women are more likely to experience sexual harassment in some work settings than others; specifically, work settings that have a large proportion of male workers, include a predominance of male supervisors, and represent traditional male occupations may be places in which there is greater tolerance for sexual harassment. The focus of the study was to document attitudes toward women among military personnel, to identify demographic and military characteristics associated with more positive attitudes toward wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 45 publications
0
40
0
1
Order By: Relevance
“…To this end, Vogt, Bruce, Street, and Stafford (2007) surveyed more than 2,000 reservists and national guards and found that poorer attitudes toward women predicted tolerance of sexual harassment and were more likely in men, ethnic majority members, and Marines. An earlier study revealed an association between negative attitudes toward women, including a lack of acceptance of women as equals in the Army, and tolerance of sexual harassment (Rosen & Martin, 1998b).…”
Section: What About the Prevention Of Mst?mentioning
confidence: 98%
See 1 more Smart Citation
“…To this end, Vogt, Bruce, Street, and Stafford (2007) surveyed more than 2,000 reservists and national guards and found that poorer attitudes toward women predicted tolerance of sexual harassment and were more likely in men, ethnic majority members, and Marines. An earlier study revealed an association between negative attitudes toward women, including a lack of acceptance of women as equals in the Army, and tolerance of sexual harassment (Rosen & Martin, 1998b).…”
Section: What About the Prevention Of Mst?mentioning
confidence: 98%
“…Rosenfeld (2002); David et al (2004); M. E. Hall et al (2007); Houser (2007); Kelley et al (2005); Leskela et al (2001); Raiha (1983); Ritchie (1998); Rosen & Martin (1998b); Valente & Wright(2007);Vogt et al (2007);Young (1995) …”
mentioning
confidence: 96%
“…According to this perspective, SH occurs in maledominated workplaces because a woman's gender is a salient, singular and distinctive feature, while in female-dominated work environments, her sex role becomes a more salient feature than her work role (Gutek and Morasch 1982). Vogt et al (2007) suggest that male-dominated work settings are rife for SH because they place a high value on masculine qualities such as power, toughness, dominance, aggressiveness and competitiveness -settings in which women may disrupt the masculine camaraderie that infuses the culture. In such settings, women and ethnic minority groups are perceived as organizational interlopers, potentially reducing the benefits that belong to the hegemonic group (white males), thereby triggering higher rates of harassment (Bergman and Henning 2008).…”
Section: Theories Guiding Sh Researchmentioning
confidence: 99%
“…However, the effect sizes for these demographic factors are generally modest (Suarez & Gadalla ), and when variance is reported, it tends to be low (See, for example, Carlson & Worden ; Worden & Carlson ; Vogt et al. ).…”
Section: Literature Reviewmentioning
confidence: 99%